Urban Sprawl and Air Quality in European Cities: an Empirical Assessment - Federica Cappelli; Gianni Guastella; Stefano Pareglio (Fondazione Eni Enrico Mattei (FEEM), 2021)
In this paper we estimate the relationship between urban sprawl and a measure of air quality, namely the number of days in which the PM10 concentration exceeds safeguard limits in European Union cities. Building on a multidimensional representation of sprawl, the paper employs several indicators to account for built-up area development, population density, and residential discontinuity. The paper employs generalised additive models to disentangle the non-linear effects in the variables and the interaction effects of the three sprawl dimensions. A significant and robust effect of urban morphology emerges after controlling for socio-economic, demographic, and climatic factors and the geographical location of the city. We find that urban sprawl impacts positively on pollutant concentration, but the effect is highly context-specific because of threshold effects and interactions.
Keywords: Q53; R14; C21; 330; Air Pollution; Urban Sprawl; European Cities; Additive Models